Short Communication: Crab species distribution under mangrove stands in Tabongo, Gorontalo Province, Indonesia - ABUBAKAR SIDIK KATILI; RAMLI UTINA; NURKNALIXA L. MOPANGGA (Biodiversitas Journal of Biological Diversity, 2017)
Katili AS, Utina R, Mopangga NL. 2017. Short Communication: Crab species distribution under mangrove stands in Tabongo, Gorontalo Province, Indonesia. Biodiversitas 18: 520-524. The aim of the study was to determine the distribution pattern of crabs under mangrove stands in the Tabongo Village, Dulupi Sub-district, Boalemo District, Gorontalo Province, Indonesia. The survey method was used for the study and data retrieved by using line transect techniques. The distribution pattern was calculated by using an index with the formula Morisita distribution patterns. The environmental factors such as temperature, salinity, and pH were measured at each stand of mangroves. The results showed that the distribution pattern of crabs in stands of Rhizophora mucronata with a value of distribution index highest for Uca triangularis (Id = 1.4) followed by Scylla olivacea (Id = 1.24), Uca annulipes (Id = 1.2) and Uca dussumieri (Id = 1.12). Uca vocans (Id = 1.08) showed the lowest value of distribution index. In Ceriops tagal stand, Uca triangularisâ€™s value of distribution index was highest (Id = 1.24) followed by Uca dussumieri (id = 1.15), Scylla olivacea (Id = 1.08) and Uca annulipes (Id = 1.06). The lowest value was noted in Uca vocans (Id = 1,04). In stands of Rhizophora stylosa value of distribution index was highest for Uca dussumieri (Id = 1.16) followed by Scylla olivacea (Id = 1.12) and Uca triangularis (Id = 1,12). The lowest value of distribution index was noted in Uca vocans and Uca annulipes (Id = 1.08). In stands of Sonneratia alba, the value of distribution index was highest for species Uca triangularis (Id = 1.2), Uca vocans (Id = 1,12) and Uca dussumieri (Id = 1.12). The lowest was noted in Scylla olivacea (Id = 1.08). Besides, the value of distribution index showed that the pattern of distribution in the study area was clumped.